Are Islamic Banks more Stable than Conventional banks? Evidence from the Indonesian Bank - Novita Trinanda Putri; Rosana Eri Puspita (Mutanaqishah: Journal of Islamic Banking, 2023)
This study aims to analyze the effect of capital adequacy, profitability, and liquidity on bank stability in Indonesia. In this study, the dependent variable was measured using Z-Score as a projection of bank stability. The sampling technique used is purposive sampling, with the criteria of the ten largest banks in Indonesia registered with the OJK and publishing their financial statements from 2018-2022. From these criteria, 20 banks were obtained, consisting of 10 conventional and 10 Islamic banks. The data analysis techniques used are panel data regression techniques and independent sample t-tests with the help of Microsoft Excel, SPSS, and Eviews. The result of this study is that profitability has a positive and significant effect on the stability of Islamic banks but not conventional banks. Liquidity has a significant negative effect on the stability of conventional banks and Islamic banks. Meanwhile, capital adequacy does not have a positive and insignificant effect on the stability of conventional banks. CAR has a significant negative effect on the stability of conventional but has no positive and insignificant effect on the stability of Islamic banks. From the average difference test, evidence was obtained that there was no significant difference between profitability, liquidity, and capital adequacy in conventional and Islamic banks. Sharia banks are more stable than conventional banks. This study suggests that banks must maintain financial stability to maintain monetary stability because the banking sector dominates financial system stability in Indonesia. The novelty of this study is the use of the latest data.